Irrational Use of Antimicrobials in Poultry Farms and Antimicrobial Resistance: A Cross-Sectional Study - Alhouzani, Talal; Saleem, Mohammad; Sharma, Arun; Khadka, Sitaram; Gupta , Ravi Prasad; Aryal, Pallav (Europasian Journal of Medical Sciences, 2025)
Background: The rampant use of antimicrobials in poultry farms is creating a global public health threat as antimicrobial resistance (AMR) in humans may arise from such practice. This study was conducted with the objective of quantification and hence assessment of the level of antimicrobial use in Pakistani poultry farms so that appropriate utilization of such agents can be assured. Methods: Six randomly selected poultry farms of Pakistan with ten production cycles with 20,000- 30,000 birds in every production cycle were selected for the study from 2018 to 2019. The average dosage utilized on-farm was described by the defined daily dose (DDD) and used daily dose (UDD). Results: It was found that enrofloxacin, amoxicillin, doxycycline, tylocin, and lincomycin were the antimicrobials commonly used by all poultry farms. However, only Enrofloxacin (UDD/DDD = 0.95) was being used within the rational therapeutic range. All the antimicrobials were used irrationally without proper indication and suggestion by the veterinarian. No records on antimicrobials use were found on any farm. Conclusion: The irrational use of antimicrobials in poultry farms may lead to antimicrobial resistance which has been a global public health threat. The speedy action should be implemented to discourage such rampant use of drugs in poultry farms in Pakistan and countries with similar farming practices for the effective use of antimicrobials in the proper indication.